2018
DOI: 10.2478/aiht-2018-69-3137
|View full text |Cite
|
Sign up to set email alerts
|

Occupational exposure to cytotoxic drugs: the importance of surface cleaning to prevent or minimise exposure

Abstract: Healthcare workers who prepare or administer cytotoxic agents run the risk of exposure, and the risks for health are real even at doses lower than those applied in cancer patients, because, in theory, no dose is safe. The most common and problematic route of exposure is through the skin, especially as work surfaces can remain contaminated even after cleaning. This pilot study aimed to demonstrate the importance of having an effective surface decontamination protocol by determining surface contamination with cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 66 publications
(79 reference statements)
0
15
0
Order By: Relevance
“…In published studies, the proportion of cyclophosphamide-positive surface samples has ranged from 17.2% to 83%. 16,17,[19][20][21][22] Although cyclophosphamide was the third most commonly used drug in our study, the median amount of cyclophosphamide used by hospitals in our study was 6.7 times lower than the median amount for 5-FU (281 g vs. 1885 g). In terms of trace contamination, the proportion of cyclophosphamide-positive samples was higher than the proportion of 5-FU-positive samples (32.4% vs. 8.5%).…”
Section: Discussionmentioning
confidence: 90%
“…In published studies, the proportion of cyclophosphamide-positive surface samples has ranged from 17.2% to 83%. 16,17,[19][20][21][22] Although cyclophosphamide was the third most commonly used drug in our study, the median amount of cyclophosphamide used by hospitals in our study was 6.7 times lower than the median amount for 5-FU (281 g vs. 1885 g). In terms of trace contamination, the proportion of cyclophosphamide-positive samples was higher than the proportion of 5-FU-positive samples (32.4% vs. 8.5%).…”
Section: Discussionmentioning
confidence: 90%
“…No cleaning product was able to remove 100% of the cyclophosphamide applied, as reported by other groups. 6,8…”
Section: Discussionmentioning
confidence: 99%
“…These authors also pointed to contamination in areas regularly used by staff or patients (“high touch” areas). 8 It is therefore important to review procedures for cleaning contaminated areas, with emphasis on cleaning several times during the day and targeting areas at high risk of contamination.…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to mycotoxins does not always have to be related to food consumption. There are studies [14][15][16][17][18][19][20][21][22] that explored the occurrence of mycotoxins in working or living environments and the results showed that exposure to mycotoxins can be related to these places too. This will be further discussed in Section 2.…”
Section: Overviewmentioning
confidence: 99%